Analysis of complex, beam-sensitive materials by transmission electron microscopy and associated techniques. (26th October 2020) - Ilett, Martha; S'ari, Mark; Freeman, Helen; Aslam, Zabeada; Koniuch, Natalia; Afzali, Maryam; Cattle, James; Hooley, Robert; Roncal-Herrero, Teresa; Collins, Sean M.; Hondow, Nicole; Brown, Andy; et al.
Abstract : We review the use of transmission electron microscopy (TEM) and associated techniques for the analysis of beam-sensitive materials and complex, multiphase systems in-situ or close to their native state. We focus on materials prone to damage by radiolysis and explain that this process cannot be eliminated or switched off, requiring TEM analysis to be done within a dose budget to achieve an optimum dose-limited resolution. We highlight the importance of determining the damage sensitivity of a particular system in terms of characteristic changes that occur on irradiation under both an electron fluence and flux by presenting results from a series of molecular crystals. We discuss the choice of electron beam accelerating voltage and detectors for optimizing resolution and outline the different strategies employed for low-dose microscopy in relation to the damage processes in operation. In particular, we discuss the use of scanning TEM (STEM) techniques for maximizing information content from high-resolution imaging and spectroscopy of minerals and molecular crystals. We suggest how this understanding can then be carried forward for in-situ analysis of samples interacting with liquids and gases, provided any electron beam-induced alteration of a specimen is controlled or used to drive a chosen reaction. Finally, we demonstrate that cryo-TEM of nanoparticle samples snap-frozen in vitreous ice can play a significant role in benchmarking dynamic processes at higher resolution. This article is part of a discussion meeting issue 'Dynamic in situ microscopy relating structure and function'.